Strategi Strategies For Octopus Fishermen'S Livelihoods In Linau Village, Maje Sub-District, Kaur Regency - Adrian Delpana; Herri Fariadi; Rika Dwi Yulihartika (UNIVED Press, Dehasen University Bengkulu, 2026)
Purpose : To analyze pre-octopus season livelihood strategies and income of octopus fishermen, understanding socio-economic adaptations and household resilience contributions. This study is vital for coastal development policies. Methodology: Qualitative approach using in-depth interviews, observation, and income formulas. Results: Strategies include job diversification (fish fishing, labor, farming, side businesses), seasonal migration, and social strategies (cooperative savings, government aid, collaborations). Average gross daily income Rp251,429; monthly Rp5,382,143, influenced by seasons and weather. Findings: These adaptations sustain household economies. Novelty: Analysis of pre-season strategies in Linau Village context. Originality: Integrated qualitative-quantitative perspective on seasonal octopus fishermen. Conclusion: Diversification and social strategies are effective; recommendations include strengthening cooperatives and sustainable diversification. Type of Paper : Case study.